The Virtue of Moderation and Environmental Ethics - Airoboman, Felix Ayemere (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
This study is a contemporary revisit to the ancient philosophical concept of moderation, and how it impinges on environmental ethics in contemporary time. The study attempts a concise but clear conceptual analysis of the concept of moderation. It inquires critically into the conceptions, which some ancient philosophers (Aristotle and Epicurus) have on it and how they raised it to the status of virtue. The study agrees with Aristotle on his doctrine of moderation, but dissents with his requirement for virtuousness for its excessive rigidity, which would make it impossible to be virtuous in moral sphere.  Thereafter the study presents Epicurusâ€™ argument that one can only achieve the goal of life through pleasure which results from moderation. It then attempts an extension and application of the concept to both theory and practice with specific references to politics and law and holds that to be virtuous in these regards is to avoid extremes and adopt the practice of moderation. Thereafter, the study focuses on environmental ethics. It attempts a brief analysis of the meaning of environmental ethics. It argues that although people have been concerned about environmental care since ancient period, environmental ethics as an academic discipline in contemporary time result mainly from the threat which result from anthropogenic impact on nature. It argues that although there is serious threat resulting from human interaction with nature, this does not justify prohibition of interaction with nature; rather, it calls for moderation to ensure genial living, as well as to ensure the preservation and sustainability of the environment and its resources. It concludes by highlighting succinctly the relevance of moderate living and moderate use of material possession and environmental resources. Finally, it opines that the ability to apply moderation appropriately to concrete issues is a virtue. Keywords : Moderation, Mental and sensual pleasures, Virtue and vice, Politics, Justice, Environmental ethics, Ecosophy, Eco-ism